Assessment of carotid atherosclerosis disease as an incremental predictive value for cardiovascular disease risk - Sidhi Laksono; Hillary Kusharsamita (Vascular Investigation and Therapy, 2023)
Assessment of the carotid atherosclerosis disease can give a prognostication of a patient's cardiovascular risk. The assessment of carotid atherosclerosis is essential because of the complication of risk factors resulting in severe cardiovascular disease (CVD). This review article aims to summarize systematically the pathophysiology, followed by diagnostic assessment and therapeutic uses of imaging and treatment for carotid atherosclerosis disease. Duplex ultrasound (DUS) of the carotid artery, transcranial Doppler imaging, computed tomographic angiography (CTA), magnetic resonance angiography, and cerebral digital subtraction angiography are diagnostic techniques for carotid stenosis. Currently, DUS of the carotid arteries is the primary screening method for carotid stenosis. Recent interest has focused on carotid intima-media thickness measurements as a possible indicator of early-stage carotid atherosclerosis or CVD risk prediction. Through the growing fields of stress tests and carotid plaque screening, the classification of cardiovascular risk may be improved.